NFKB1 gene rs28362491 ins/del variation is associated with higher susceptibility to myocardial infarction in a Chinese Han population - Luo, Jun-Yi (Sci Rep, 2020)
Myocardial infarction (MI), the leading cause of mortality and disability worldwide, is a disease in which multiple environmental and genetic factors are involved. Recently, researches suggested that insertion/deletion (ins/del) variation of NFKB1 gene rs28362491 is a functional polymorphism. In the present study, we aimed to explore the relation between variation of NFKB1 gene rs28362491 and MI by polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) in 359 MI patients and 1085 control participants. Gensini score was used to evaluate the degree of coronary artery stenosis in MI patients. The plasma levels of interleukin-6 (IL-6), IL-8, malonaldehyde (MDA) and superoxide dismutase (SOD) were randomly measured by ELISA both in MI patients and control participants. We found that the detected frequencies of D allele (41.2% vs. 36.4%, P = 0.021) and DD genotype (17.5% vs. 12.0%, P = 0.022) were significantly higher in MI patients than in control participants. Compared with II or ID genotype carriers, the Gensini score in MI patients with DD genotype was 32–43% higher (both P < 0.001). Moreover, DD genotype carries had more diseased coronary arteries (P = 0.001 vs. II or ID genotype). Of note, IL-6 levels in MI patients carrying DD genotype were significantly higher than that in control participants and other genotype carriers in MI patients (both P < 0.05). In conclusion, NFKB1 gene rs28362491 DD genotype was associated with a higher risk of MI and more severe coronary artery lesion, which also had a potential influence on the level of inflammatory cytokine IL-6.